ANalisis Semiotika Dan Pesan Moral Dalam Film Kkn Di Desa Penari - Dimas Cahaya Putra; Nurseri Hasnah Nasution (CV. ITTC INDONESIA, 2023)
This research discusses the meaning of the moral messages contained in the scenes in the KKN film in Penari Village. KKN in Penari Village was adapted from a horror story that went viral in 2019 and according to the author, this story was taken from a true story. This horror genre film is a film series that tells the story of a group of students who are undertaking a Community Service Program (KKN) in Penari Village. The KKN program they created did not run smoothly, a series of horror experiences haunted them until the KKN program ended tragically. In this film, the author analyzes all the scenes from the beginning to the end of the film. This type of research is a type of qualitative descriptive research using Roland Barthes' semiotic theory. Therefore, in this research the author used data collection techniques which were carried out with documentation, namely by collecting scenes in the KKN film in Penari Village which contained signs of the meaning of the moral message. The literature study used is data or information obtained by the author through journals, theses, books, articles, etc. that can support this research. From this research, the results obtained are that the KKN Film in Penari Village has deep meanings in Denotation, Connotation, Myth and Moral Message.